Plain English (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Beating around the bush sucks. Trying to understand a sentence from someone who has swallowed a thesaurus, or worse, a politician, can make your head spin. As far back as 1600, in Hamlet, Shakespeare wrote the memorable lines 'more matter, with less art' and 'brevity is the soul of wit'. The problem is that unclear writing plagues us every day. So many decisions are made worldwide based on a partial understanding because the available explanations were confusing and unclear. Writing in plain language allows your message to reach as many people as possible. Clear writing can also avoid misunderstandings, that may have serious consequences. In this track, we give you practical tips on how to use Plain English to improve your business communication. Learning Objectives Learn about the benefits of Plain English when communicating Learn how to implement Plain English techniques Learn to get your point across succinctly.